Dampak Pernikahan Dini Ditinjau Dari Sudut Pandang Sosial Dan Pendidikan - Teddy Pascha S. Depari, Rifki Aditya, Julia Ivanna (Education Achievement: Journal of Science and Research, 2023)
Marriage is an activity that changes something that is unlawful to become lawful with the legal requirements of a marriage having been fulfilled, but what has become a phenomenon in Indonesia, especially in South Kalimantan, is the high number of early marriages that occur. This is because there are some thoughts from the community that by marrying off their child immediately, they no longer need to take care of the maintenance for the child, releasing their responsibilities as parents, what if the child is a girl. In Indonesia, the requirement for a person to marry is when a woman reaches the age of 16 (sixteen) years, while for a man 19 (nineteen) years this is stated in the law on marriage. Early marriage is a marriage carried out by a pair of teenagers (male and female) who are less than 20 years old and immature physically, physiologically and psychologically. Early marriages that occur are generally carried out by young women. The method used in this research is the Qualitative Method of Library Studies. Early marriages that occur in women are caused by educational and cultural factors. Early marriage also has an impact, namely the impact on the individual who does it, the impact on his family and the community or country.